2020
DOI: 10.3390/ijms21186694
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis to Study the Relationship between Tumor-Associated Selenoproteins: Focus on Prostate Cancer

Abstract: Selenoproteins are proteins that contain selenium within selenocysteine residues. To date, twenty-five mammalian selenoproteins have been identified; however, the functions of nearly half of these selenoproteins are unknown. Although alterations in selenoprotein expression and function have been suggested to play a role in cancer development and progression, few detailed studies have been carried out in this field. Network analyses and data mining of publicly available datasets on gene expression levels in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…In the present study, by integrating bothin silicoand wet lab approaches, we demonstrated that the expression profiles of five selenoproteins are specifically dysregulated in TNBC. Most importantly, by bioinformatics analysis, we selected SELENOS and its interacting protein VCP/p97 as inter-related with the others and whose coordinated overexpression is associated with poor prognosis in TNBC.Overall, we confirmed, as previously suggested [12], that only the combined evaluation of some selenoproteins and of HUB nodes could have prognostic value and may improve patient outcome prediction.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In the present study, by integrating bothin silicoand wet lab approaches, we demonstrated that the expression profiles of five selenoproteins are specifically dysregulated in TNBC. Most importantly, by bioinformatics analysis, we selected SELENOS and its interacting protein VCP/p97 as inter-related with the others and whose coordinated overexpression is associated with poor prognosis in TNBC.Overall, we confirmed, as previously suggested [12], that only the combined evaluation of some selenoproteins and of HUB nodes could have prognostic value and may improve patient outcome prediction.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, to better define the correlation between the selenoprotein family and cancer, we took advantage of a bioinformatics approach and studied the interaction network between all twenty-five selenoproteins, highlighting the presence of six HUB nodes (ABL1, EP300, FYN, MYC, PSMB2 and SRPK2) that play the strongest role in coordinating the obtained network. Within this analysis, we also analyzed the correlation between some selenoproteins and/or HUB node gene expression and patient outcome in ten solid tumors [12]. Moreover, we evaluated the gene expression levels of the twenty-five selenoproteins and of the six HUB nodes identified in four prostate cancer cell lines compared to normal prostate epithelial cells, selecting three selenoproteins (GPX2, EP300 and PSMB2), whose collective expression correlated with the overall survival of prostate cancer patients, suggesting that only the combined evaluation of some selenoproteins and HUB nodes could have prognostic value and may improve patient outcome prediction [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation